The APTT Monitoring of Heparin - The ISTH/ICSH Collaborative Study - Poller, L; Van der Velde, E A (Thrombosis and Haemostasis, 1995)
In an international collaborative study three candidate reference and the local APTT reagent have been tested with lyophilized plasmas containing heparin added in vitro and fresh plasmas from heparinized patients to determine whether it was possible to standardize APTT heparin monitoring.The APTT responses of patients with thrombosis were much less to the same concentrations of heparin so only these plasmas were used to calibrate the reagents.A calibration constant (b) was determined for each local APTT system from the orthogonal regression slope of the patients’ and normals’ plasmas. Although the calibration was based on relatively limited numbers of patients’ plasmas the results gave no consistent indication that this method of analysis with the reference preparations was incorrect. Two of the three candidate reference reagents performed almost equally well and one of these reagents is recommended as the APTT reference preparation. Use of a single b value for a brand of reagent for all laboratories is not advised. Each laboratory must perform its own local calibration. The adoption of a reference APTT reagent together with the use of orthogonal regression analysis would be a useful step to initiate APTT heparin monitoring standardization and to develop safe and effective local therapeutic ranges.